First‐pass myocardial perfusion imaging with whole‐heart coverage using L1‐SPIRiT accelerated variable density spiral trajectories. Issue 5 (5th November 2015) - Yang, Yang; Kramer, Christopher M.; Shaw, Peter W.; Meyer, Craig H.; Salerno, Michael
Abstract : Purpose: To design and evaluate two‐dimensional (2D) L1‐SPIRiT accelerated spiral pulse sequences for first‐pass myocardial perfusion imaging with whole heart coverage capable of measuring eight slices at 2 mm in‐plane resolution at heart rates up to 125 beats per minute (BPM). Methods: Combinations of five different spiral trajectories and four k‐t sampling patterns were retrospectively simulated in 25 fully sampled datasets and reconstructed with L1‐SPIRiT to determine the best combination of parameters. Two candidate sequences were prospectively evaluated in 34 human subjects to assess in vivo performance. Results: A dual density broad transition spiral trajectory with either angularly uniform or golden angle in time k‐t sampling pattern had the largest structural similarity and smallest root mean square error from the retrospective simulation, and the L1‐SPIRiT reconstruction had well‐preserved temporal dynamics. In vivo data demonstrated that both of the sampling patterns could produce high quality perfusion images with whole‐heart coverage. Conclusion: First‐pass myocardial perfusion imaging using accelerated spirals with optimized trajectory and k‐t sampling pattern can produce high quality 2D perfusion images with whole‐heart coverage at the heart rates up to 125 BPM. Magn Reson Med 76:1375–1387, 2016. © 2015 International Society for Magnetic Resonance in Medicine